Caring for the dead in ancient Israel - Sonia, Kerry M. (2020)
"In Caring for the Dead in Ancient Israel, Kerry M. Sonia examines the commemoration and care for the dead in ancient Israel against the broader cultural backdrop of West Asia. This cult of dead kin, referred to as ancestor cult in some previous studies, in ancient West Asia comprised a range of ritual practices in which the living provided food and drink offerings, constructed commemorative monuments, invoked the names of the dead, and protected their remains"--
The Israelite Cult of Dead Kin in its Ancient West Asian Context -- Necromancy and the Cult of Dead Kin in Ancient West Asia -- The Role of Women in the Israelite Cult of Dead Kin -- The Status of the Cult of Dead Kin in the Post-exilic Period.
Includes bibliographical references and index.
Keywords: Death -- Palestine; Dead -- Religious aspects -- Judaism; Ancestor worship -- Palestine; Ancestor worship -- Middle East; Funeral rites and ceremonies, Ancient -- Palestine -- History; Funeral rites and ceremonies, Ancient -- Middle East -- History; Jewish funeral rites and ceremonies -- Palestine